Editorial: Talent Identification and Development in Sports Performance - Leite, Nuno (2021)
Talent identification and development have become increasingly relevant in sports performance (Sarmento et al., 2018), especially in the last 20 years. A significant body of scientific research discusses longitudinal and non-linear talent identification and development processes, the qualities that underpin elite performance in sport, and how coaches could facilitate talented athletes' development through the sports system (Baker et al., 2020). Yet it can be argued that the continued interest in talent identification and development reflects the persistently low predictive value of applied and theoretical talent identification models (Till and Baker, 2020). Finding, recruiting, and retaining talent is a global challenge, and it is especially relevant for sports clubs and national federations that often see potential assets escape due to self-system inefficiencies (Koz et al., 2012). In point of fact, original research selected for this topic confirmed that talent development programs should make conscious decisions about their selection strategies as it can affect their success (Kalén et al.; Dugdale et al.).